Pematahan Dormansi dan Perkecambahan Biji Kopi Arabika (Coffea arabika L.) dengan Asam Sulfat (H2SO4) dan Giberelin (GA3) - Mukarlina, Devi Lestari, Riza Linda, (Jurnal Protobiont, 2016)
Arabica coffee (Coffea arabica L.) is one of the commodities witha high economic value. The production of the arabica coffee plant (C. arabica L.) is influenced by seed dormancy. This research aimed to find out the effect of sulfuric acid (H2SO4) and gibberellin (GA3) in accelerating the dormancy breaking and germination of the seeds of arabica coffee (C. arabica L.). This research used a completely randomized design (CRD), which consisted of two factors. The first factor was the concentration of H2SO4consisting of 5 treatments, i.e. the concentration of 0% (A0), 5% (A1), 10% (A2), 15% (A3), and 20% (A4). The second factor was the concentration of 0 ppm GA3 0 ppm (B0), 20 ppm (B1), 40 ppm (B2), 60 ppm (B3), dan 80 ppm (B4). Each treatment was repeated 3 times, so 75 experimental units were obtained. Data were analyzed using ANOVA (Analysis of Variance) and a further test using the Duncan test. The research findings showed thatthe treatment of sulfuric acid (H2SO4) at concentration of 10% was the best concentration for accelerating the growth ofthe seed of arabica coffee (C. arabica L.) with a percentage of 57.18%. The combination of sulfuric acid (H2SO4) of 10% and gibberellin (GA3) of 40 ppm was the best concentration for the growth of germination of arabica coffee (C. arabica L.) with a percentage of 38%.